Esophageal adenocarcinoma and squamous cell carcinoma in children and adolescents: Report of 3 cases and comprehensive literature review - Till M. Theilen; Alexander J. Chou; David S. Klimstra; Michael P. LaQuaglia (Elsevier, 2016)
Malignant esophageal tumors are exceedingly rare in children and adolescents. We present 3 cases of esophageal adenocarcinoma (AC) and squamous cell carcinoma (SSC) in patients ≤21 years of age who were treated at our institution between 1950 and 2015. We also undertook an analysis of those cases, combined with cases from a review of the literature, to examine patient demographics, disease characteristics, and outcomes. We identified one patient with AC and two patients with SCC treated at our institution, as well as 19 cases of AC (median age 16) and 23 cases of SCC (median age 15) reported in the literature. Male predominance was noted at a ratio of 2.2 to 1. Dysphagia, weight loss, and anemia were the most common presenting symptoms for both entities. Approximately 84% of AC tumors were located in the distal esophagus and gastroesophageal junction whereas SCC tumors were distributed evenly throughout esophagus. Metastatic disease at presentation was found in 68.4% of patients with AC compared to 30.4% of those with SCC. Survival was not significantly different between SCC and AC (P = 0.36), between genders (P = 0.13), and between patients treated with surgery vs. multimodality therapy (P = 0.15). Metastasis, however, predicted worse outcome (P = 0.0019). We found that adolescent AC and SCC show characteristics similar to such tumors when presenting in adults. Though extremely rare in the adolescent population, these malignant diseases should always be ruled out when young patients present with a short history of dysphagia with signs of clinical deterioration.